Is capitalism still viable? - Kirk, Russell (Journal of business ethics, 1982)
This essay is an attempt to clarify the meaning of ‘capitalism’ and to argue that this form of economic pattern will survive in the U.S. in the twentieth century. Capitalism should not be viewed as an abstraction which implies a religion, an ideology, a form of government, or a moral philosophy, but rather “the private ownership of capital”. Marx was wrong when he predicted the speedy decay of the ‘capitalistic system’ in the West and when he claimed that a competitive system will lead to servitude and poverty for the masses; on the contrary, the American economic system is a grand success. Part of this success resulted “from natural resources; part from America's being one of the largest free-trade areas; and part from the economic system, so-called ‘capitalism’, by which we have governed ourselves”. The outcome is a greater measure of freedom, prosperity, leisure, and industrial sophistication. These achievements are hardly paralleled by any of the advanced countries of the world.